Distinct Thalamo‐Subcortical Circuits Underlie Painful Behavior and Depression‐Like Behavior Following Nerve Injury - Jie Deng; Li Chen; Cui‐Cui Liu; Meng Liu; Guo‐Qing Guo; Jia‐You Wei; Jian‐Bo Zhang; Hai‐Ting Fan; Zi‐Kun Zheng; Pu Yan; Xiang‐Zhong Zhang; Feng Zhou; et al. (Advanced Science)
Abstract Clinically, chronic pain and depression often coexist in multiple diseases and reciprocally reinforce each other, which greatly escalates the difficulty of treatment. The neural circuit mechanism underlying the chronic pain/depression comorbidity remains unclear. The present study reports that two distinct subregions in the paraventricular thalamus (PVT) play different roles in this pathological process. In the first subregion PVT posterior (PVP), glutamatergic neurons (PVPGlu) send signals to GABAergic neurons (VLPAGGABA) in the ventrolateral periaqueductal gray (VLPAG), which mediates painful behavior in comorbidity. Meanwhile, in another subregion PVT anterior (PVA), glutamatergic neurons (PVAGlu) send signals to the nucleus accumbens D1‐positive neurons and D2‐positive neurons (NAcD1→D2), which is involved in depression‐like behavior in comorbidity. This study demonstrates that the distinct thalamo‐subcortical circuits PVPGlu→VLPAGGABA and PVAGlu→NAcD1→D2 mediated painful behavior and depression‐like behavior following spared nerve injury (SNI), respectively, which provides the circuit‐based potential targets for preventing and treating comorbidity.